Сиреневая даль: [стихи] / Виталий Иродов ; [художник В. Ю. Семенов] - Иродов Виталий Олегович (Удмуртия, 2017)
Экземпляры: РБаб (20191023) / Инвентарный номер: 51169 / Цена: 80.00 / Авт.знак: И 83 / ББК: 84(2Рос=Удм)6